Patofisiologia de osteonecrose induzida por bisfosfonatos e inibidores de RANK-L - Molon, Rafael Scaf de [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The pathogenesis of the osteonecrosis of the jaw (ONJ) and its risk factors still remain poorly understudied and continue to be the focus on ongoing studies to establish a proper diagnosis, prevention and treatment. Thus, the aims of this study were: (1) to develop in mice, an experimental model of osteonecrosis induced by bisphosphonates (BPs) and RANK-L inhibitors associated with spontaneously periodontal disease. Then, (2) using the same experimental model in mice, to investigate if the discontinuation of these drugs alters the clinical and radiographic features of ONJ. In addition, (3) the influence of systemic diseases such as rheumatoid arthritis (RA), and ONJ was assessed as a possible risk factor for worsening ONJ characteristics. The analyses in all studies were established through radiographic, by means of micro-computed tomography, and histological assessments. In the first study, a new experimental animal model using different antiresorptive drugs was established with clinical features similar to what occurs in humans, with extensive necrotic areas and exposed bone o the oral cavity. The results of the study 2 showed that discontinuing OPG-Fc, a RANK-L inhibitor, but not BPs reversed all the clinical and radiographic features of ONJ. Furthermore, the results of study 3 suggest that treatment with high doses of BPs associated with the presence of RA exacerbated the incidence and severity of ONJ in mice. These data evidenced that BPs and RANK-L inhibitors possess great similarity in the radiographic and histologic findings, including the incidence of osteonecrosis and bone exposure, but only the OPG-Fc discontinuation completely reverses ONJ features. The data further support the relevance of RA as a risk factor for ONJ development.

A patogênese de osteonecrose dos maxilares (ONJ) e os fatores de risco ainda não estão totalmente elucidados e continuam sendo foco de contínuos estudos visando estabelecer um correto diagnóstico, prevenção e tratamento. Assim, os objetivos do presente estudo foram: (1) desenvolver em camundongos, um modelo experimental de ONJ induzido por bisfosfonatos (BPs) e inibidores de RANK-L associado a doença periodontal espontânea; (2) investigar neste modelo se a descontinuação desses medicamentos alteraria as características clinicas e radiográficas de osteonecrose e, (3) avaliar a influência da artrite reumatoide (AR) no agravamento de ONJ experimental. As análises em todos os estudos foram estabelecidas por meio de avaliações radiográficas, por microtomógrafo, e histológicas. No primeiro estudo, foi estabelecido um novo modelo experimental animal utilizando-se diferentes medicamentos anti-reabsortivos, resultando em características clinicas semelhantes ao que ocorre em humanos, ou seja, extensas áreas necróticas e com exposição óssea a cavidade oral. Os resultados do estudo 2 demonstraram que a descontinuação de OPG-Fc, um inibidor de RANK-L, mas não de BPs reverteu todas as características clinicas e radiográficas de ONJ. Além disso, os resultados do estudo 3 sugerem que a AR associada ao tratamento com altas doses de BPs exacerba a incidência e a severidade de ONJ em camundongos. Com base nos achados do presente estudo, conclui-se que ONJ induzida por BPs e por inibidores de RANKL como OPG-Fc e RANK-Fc apresentam grande similaridade nas características radiográficas e histológicas, entre si e com a doença em humanos, mas somente a descontinuação do tratamento com OPG-Fc leva a uma reversão completa das alterações clinicas da doença. Os dados suportam a relevância da AR como um fator de risco para o desenvolvimento de ONJ.
Pathophysiology of osteonecrosis of the jaws induced by bisphosphonates and RANK-L inhibitors
Keywords: Alveolar bone loss; Mice; Osteoclasts; Periodontal disease; Rheumatoid arthritis; Perda óssea alveolar; Camundongos; Osteoclasto; Doenças periodontais; Artrite reumatoide